2009
DOI: 10.1098/rspa.2009.0050
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic activity of polyamidoamine dendrimers and the protective role of human serum albumin

Abstract: We have examined the haemolytic activity of polyamidoamine dendrimers. Haemolysis increased in a generation-and concentration-dependent manner. Moreover, the longer the incubation time, the greater the amount of haemoglobin released. When human serum albumin (HSA) was present in the incubation buffer, the extent of haemolysis decreased. This protective effect may be due to the high affinity of dendrimers for proteins: dendrimers that interact with HSA are unable to disrupt the membrane to the same extent as fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…proteins, in an incubation buffer might also influence RBC-dendrimer interactions. A study performed by Klajnert et al [54] indicated that the haemolytic activity of PAMAM G5 dendrimers in the presence of human serum albumin (HSA) greatly decreased the haemolysis level. This protective effect may be due to the high affinity of dendrimers for serum proteins [24,55].…”
Section: Ways To Reduce Dendrimer Haemotoxicitymentioning
confidence: 99%
“…proteins, in an incubation buffer might also influence RBC-dendrimer interactions. A study performed by Klajnert et al [54] indicated that the haemolytic activity of PAMAM G5 dendrimers in the presence of human serum albumin (HSA) greatly decreased the haemolysis level. This protective effect may be due to the high affinity of dendrimers for serum proteins [24,55].…”
Section: Ways To Reduce Dendrimer Haemotoxicitymentioning
confidence: 99%
“…Earlier studies on the interaction of PAMAM dendrimer with red blood cells have reported that the electrostatic interactions are the driving force for the red blood cell lysis when administered intravenously [11]. It has also been anticipated that PEGylation could effectively decrease the RBC membrane damage induced by PAMAM dendrimer [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, if that is done, RBCs are expected to be the first and unwanted targets of their action; in particular, hemolysis may occur. Hemolysis is the release of hemoglobin from the damaged erythrocytes (also known as red blood cells) [11]. Recently a mini-review has been focused on discussing the in vitro interactions between dendrimers and red blood cells, and pointed out the possible strategies to facilitate the dendrimer hemotoxicity [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howell (Central Michigan University;Howell & Fan 2010); an investigation on haemotoxicity of PAMAM dendrimers and the protective role of human serum albumin in haemolysis by B. Klajnert (University of Lodz; Klajnert et al 2010); and a pre-clinical and behavioural toxicity profile of PAMAM dendrimers in mice by A. S. Chauhan (Dendritic NanoTechnologies Inc.; Chauhan et al 2010). These research endeavours demonstrate control of molecular properties for a variety of biomedical applications in the design of unique dendrimer structures via organic, inorganic, organometallic and biochemistry.…”
Section: Unique Structure and Property Of Dendrimers In Biomedical Apmentioning
confidence: 99%